Biological disturbance of MiR-425 and its application prospects in cardiovascular diseases - Zhou, Shan; Han, Bo (Frontiers in Cell and Developmental Biology, 2025)
MiR-425 is a biological molecule that has potential applications in cardiovascular diseases. It can regulate biological functions by combining with LncRNAs, binding with proteins, and changing the differentiation of immune cells. MiR-425 also has a role as a biomarker of disease. In cardiovascular diseases, it has clinical significance in reducing inflammation and heart repair, inducing angiogenesis, improving the prediction of atherosclerosis, reducing cardiac fibrosis, and regulating atrial natriuretic peptide to affect cardiovascular function. Target gene prediction and KEGG enrichment analysis are also mentioned.